Evaluation of computer vocabulary for third-grade students of the Musical Arts Department (Journal of the College of Basic Education, 2023)
Computer is one of the basic academic subjects because of its importance in the field ofEducational technology and its invasion of the educational arena on the one hand, and its connection to the life of a studentArts in general, and the student of the Musical Arts Department in particular, on the other hand, where he becameThe computer is in direct contact with the music, so the offered music computer programs have becomeMoin helped to facilitate many tasks and remove most of the obstacles that were facingmusicians in the past at the level of music recording, music notation and playingtraining, authoring, and analysis.